First observation of a shape isomer and a low-lying strongly-coupled prolate band in neutron-deficient semi-magic 187Pb - W.Q. Zhang; A.N. Andreyev; Z. Liu; D. Seweryniak; H. Huang; Z.H. Li; J.G. Li; C.Y. Guo; D.T. Doherty; A.E. Barzakh; P. Van Duppen; J.G. Cubiss; et al. (Physics Letters B, 2022)
Prompt and delayed γ-ray spectroscopy of the neutron-deficient, semi-magic isotope 187Pb has been performed using the recoil-decay and isomer-decay tagging techniques at the Argonne Gas-Filled Analyzer. A new 5.15(15)-μs isomeric state at only 308 keV above the spherical 3/2− ground state is identified and classified as a shape isomer. A strongly-coupled band is observed on top of the isomer, which is nearly identical to the one built on the prolate 7/2−[514] Nilsson state in the isotone 185Hg. Based on this similarity and on the result of the potential-energy surface calculations, the new isomer in 187Pb is proposed to originate from the same configuration. The retarded character of the 308-keV (7/2−)→3/2gs− transition with a deduced B(E2)=5.6(2)×10−4 W.u. can be well explained by the significant difference between the prolate parent and spherical daughter configurations, leading to the shape isomerism. The excitation energy of the isomer is surprisingly low, being roughly half of the excitation energies of the known 0+ intruder bandheads in the neighboring 186,188Pb isotopes. The combined results of the present work and the previous α-decay and laser spectroscopy studies present evidence for triple shape coexistence at low energy in the negative-parity configurations of 187Pb, which is well reproduced by the potential-energy surface calculations.